Simulation of On-Grid PV System For Residential - Mat Nawi , Syahirah; Hamdan, Rohaiza (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, the demand for electrical energy is growing every day, yet conventional energy sources are dwindling. Alternative energy resources must be used to bridge the gap between rising demand and supply in order to close the gap. A source of renewable energy appears to be a promising option. Because of its natural availability, clean, environmentally beneficial, and an endless supply of energy, solar energy is the greatest option. By using MATLAB/Simulink software, this research presents a design and simulation of a home on-grid solar system. The system comprises of a solar array that transforms light radiation into electrical power, a boost DC-DC converter that boosts the photovoltaics’ voltage, and an on-grid photovoltaic inverter that converts DC electricity to single-phase AC power. The maximum power point tracking (MPPT) control was developed to track the solar array’s maximum power output. This project uses MATLAB/Simulink to simulate the output power when using an MPPT controller and without an MPPT controller by using a residential load. As a consequence, the suggested system has the potential to lower household power expenses